A Low ω-6 to ω-3 PUFA Ratio (n–6:n–3 PUFA) Diet to Treat Fatty Liver Disease in Obese Youth. Issue 9 (11th July 2020) - Van Name, Michelle A; Savoye, Mary; Chick, Jennifer M; Galuppo, Brittany T; Feldstein, Ariel E; Pierpont, Bridget; Johnson, Casey; Shabanova, Veronika; Ekong, Udeme; Valentino, Pamela L; Kim, Grace; Caprio, Sonia; et al.
ABSTRACT: Background: Recent literature suggests that the Western diet's imbalance between high ω-6 (n–6) and low ω-3 (n–3) PUFA intake contributes to fatty liver disease in obese youth. Objectives: We tested whether 12 wk of a low n–6:n–3 PUFA ratio (4:1) normocaloric diet mitigates fatty liver and whether the patatin-like containing domain phospholipase 3 ( PNPLA3 ) rs738409 variant affects the response. Methods: In a single-arm unblinded study, obese youth 9–19 y of age with nonalcoholic fatty liver disease were treated with a normocaloric low n–6:n–3 PUFA ratio diet for 12 wk. The primary outcome was change in hepatic fat fraction (HFF%), measured by abdominal MRI. Metabolic parameters included alanine aminotransferase (ALT), lipids, measures of insulin sensitivity, and plasma oxidized linoleic acid metabolites (OXLAMs). Outcomes were also analyzed by PNPLA3 rs738409 genotype. Wilcoxon's signed rank test, the Mann–Whitney U test, and covariance pattern modeling were used. Results: Twenty obese adolescents (median age: 13.3 y; IQR: 10.5–16.4 y) were enrolled and 17 completed the study. After 12 wk of dietary intervention, HFF% decreased by 25.8% ( P = 0.009) despite stable weight. We observed a 34.4% reduction in ALT ( P = 0.001), 21.9% reduction in triglycerides ( P = 0.046), 3.28% reduction in LDL cholesterol ( P = 0.071), and a 26.3% improvement in whole body insulin sensitivity ( P = 0.032). The OXLAMs 9-hydroxy-octadecandienoic acid (9-HODE) ( P = 0.011), 13-HODE ( P = 0.007), and 9-oxo-octadecadienoic acid (9-oxoODE) ( P = 0.024) decreased after 12 wk. HFF% declined in both the not-at-risk (CC/CG) and at-risk (GG) PNPLA3 rs738409 genotype groups, with significant ( P = 0.016) HFF% reduction in the GG group. Changes in 9-HODE ( P = 0.023), 9-oxoODE ( P = 0.009), and 13-oxoODE ( P = 0.003) differed between the 2 genotype groups over time. Conclusions: These data suggest that, independently of weight loss, a low n–6:n–3 PUFA diet ameliorates the metabolic phenotype of adolescents with fatty liver disease and that response to this diet is modulated by the PNPLA3 rs738409 genotype. This trial was registered at clinicaltrials.gov as NCT01556113.